TRAINING ACCOUNTANTS IN GREAT BRITAIN. - Lorig, Arthur N. (The Accounting Review, 1960)
Abstract The paper describes the training of accountants in Great Britain, first discussing the situation in England and Wales and later mentioning ways in which the Scottish training differs. The Institute of Chartered Accountants in England and Wales has virtual control over the admission of people into the public accounting field in those two countries. There is no separate licensing of public accountants by a government. Membership in the Institute is comparable to holding a state license to practice as a certified public accountant in this country. Members are allowed to described themselves as "chartered accountants" and to use the abbreviations F.C.A. for fellows and A.C.A. for associates. Businessmen are accustomed to seeking the services of Institute members for their professional accounting needs, and "by far the most important part of professional accounting work is carried out by chartered accountants." To become a chartered accountant one must become an articled clerk under Institute regulation and supervision for a prescribed period of years, pass examinations prepared, administered, and graded by the Institute, be accepted by the Institute council for membership.